Load analysis of dangerous freight cistern cars during gravity hump - D. A. Stupin; A. V. Savrukhin; R. A. Efimov (Вестник Научно-исследовательского института железнодорожного транспорта, 2023)
Introduction. The article considers the determination of the impact velocities of empty and loaded Class 2 dangerous freight cistern cars on a gravity hump, the forces acting on the car through the automatic coupler, as well as the accelerations acting on the loading and unloading, safety valves and elements of the tank shell interior. Currently Class 2 dangerous freight cars with Classification Code 2112 and UN numbers 1011, 1965, 1969, 1978 could be shunted over the gravity hump only with a shunting locomotive, backing off with extreme caution, without jerks or sudden stops. This limitation prevents shunting gas cistern cars on automated gravity humps, which complicates shunting operations during train formation.Materials and methods. Impact test of a cistern car alternately equipped with cushions of Classes T1, T2 and T3 with measurement of speeds, forces and accelerations.Results. The maximum permissible impact velocities of the cistern car are determined.Discussion and conclusion. According to the test results, as well as the GOST 32913–2014 requirements, the authors state that the implementation of the previously developed technology for shunting Class 2 dangerous freight cistern cars equipped with Class T3 draft gears on gravity humps, with a maximum approach speed of 3 km/h complies with shunting safety requirements.